Modeling and Simulation of Reaction Environment in Photoredox Catalysis: A Critical Review - de Oliveira, Gabriela Xavier; Lira, Jéssica Oliveira de Brito; Riella, Humberto Gracher; Soares, Cíntia; Padoin, Natan (Frontiers in Chemical Engineering, 2022)
From the pharmaceutical industry’s point of view, photoredox catalysis has emerged as a powerful tool in the field of the synthesis of added-value compounds. With this method, it is possible to excite the catalyst by the action of light, allowing electron transfer processes to occur and, consequently, oxidation and reduction reactions. Thus, in association with photoredox catalysis, microreactor technology and continuous flow chemistry also play an important role in the development of organic synthesis processes, as this technology offers high yields, high selectivity and reduced side reactions. However, there is a lack of a more detailed understanding of the photoredox catalysis process, and computational tools based on computational fluid dynamics (CFD) can be used to deal with this and boost to reach higher levels of accuracy to continue innovating in this area. In this review, a comprehensive overview of the fundamentals of photoredox catalysis is provided, including the application of this technology for the synthesis of added-value chemicals in microreactors. Moreover, the advantages of the continuous flow system in comparison with batch systems are pointed out. It was also demonstrated how modeling and simulation using computational fluid dynamics (CFD) can be critical for the design and optimization of microreactors applied to photoredox catalysis, so as to better understand the reagent interactions and the influence of light in the reaction medium. Finally, a discussion about the future prospects of photoredox reactions considering the complexity of the process is presented.